Lord of the lemons: Origin and dynamics of state capacity - Thilo R. Huning; Fabian Wahl (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2017)
To better understand the role of taxation in the emergence of states, this article presents an incomplete contract model of an agricultural society in which information asymmetries cause inefficient taxation, and hence outmigration, uprisings, and rent-seeking, but also urbanization. We propose a geographic index of information costs, observability, to test our model. Our case study is the Holy Roman Empire, which had a relatively homogeneous institutional framework, state of technology, culture, and ethnic composition across hundreds of observed states, for over 500 years. We find a robust link between observability and states' tax capacity, their size, and their survival.
urn:nbn:de:bsz:100-opus-14058
Keywords: O42; D73; Q15; N93; D82; 330; state capacity; principal-agent problem; taxation; Holy Roman Empire